An experimental study of steam generator tube loading during a two-phase blowdown - Hamouda, Ouajih (My University, 2015)
This research studies the effects of a postulated Main Steam Line Break accident in a nuclear plant on the transient loading of steam generator tubes. The problem involves complex transient two-phase flow dynamics and fluid-structural loading processes. A better understanding of this phenomenon will permit the development of improved design tools to ensure steam generator safety. This Thesis presents the results of an experimental laboratory study of the transient loading of a sectional model of steam generator tubes during a simulated two-phase blowdown. The research was carried out in a purpose designed and built experimental facility. The thermodynamic phenomena were investigated through dynamic pressures and temperatures. The transient tube loads were directly measured using dynamic load cells. The working fluid was R-134a and the tube bundle was a normal triangular array with a pitch ratio of 1.36. Preliminary testing indicated parasitic loading on the instruments and remedial actions were taken to ensure measurement accuracy. The success of the instrumentation development methodologies was validated in a series of single- phase blowdowns. Two-phase blowdown experiments were then conducted with various levels of liquid and numbers of tube rows. The results provided hitherto unknown information relating the nature of the fluid-structure interaction and flow development during a two-phase transient blowdown across a tube bundle. The pressure drop across the tube bundle established the thermal hydraulic fluid behaviour in the pressure vessel and controlled the upstream fluid discharge from the system. The flow through the bundle was choked for the majority of the transient. The transient tube loading was explained in terms of the associated fluid mechanics and the maximum load was compared with existing models obtained under steady flow conditions. An empirical model was developed that enables the prediction of the maximum tube loads once the pressure drop is known.
Keywords: Transient two-phase blowdown